LEARNING ORGANIZATION, KOMITMEN PADA ORGANISASI, KEPUASAN KERJA, EFEKTIVITAS PENERAPAN SISTEM ISO DAN DAMPAKNYA TERHADAP KINERJA ORGANISASI (STUDI KASUS STAF ADMINISTRASI UK PETRA SURABAYA) - Monica Ida Uniati (Jurnal Manajemen Pemasaran, 2014)
This research analyzes the simultaneous effects of Learning Organization (LO), Job Satisfaction, Effectiveness of ISO Implementation, Organizational Commitment on Organizational Performanace as perceived by the staff of administrative supporting units. The result of data processing shows that there is not any direct effect of LO on Orgnizational Performace. However, there is a strong positive effect of LO toward Organizational Performance through Job Satisfaction. LO does not have a direct effect on Organizational Commitment, however, the strong positive effect of LO toward Organizational Performance is formed through Job Satisfaction and Organizational Commitment. This research also found that there is a negative effect of Effectiveness of ISO Implementation on Job Satisfaction, which simultaneously weakens the effect of LO on Organizational Performance through Job Satisfaction.